Malaysian expectation towards digital banking - Soo, Chamaine Min Xin; Lew, Swit Wah; Liew, Chi Yun; Lim, Yun De; Ng, Jia Wen (2023)
Digital banking has emerged as a revolutionary force in the financial system worldwide, and Malaysia is no exception. Although digital banking has yet to be launched in Malaysia, Malaysia is on the cusp of introducing digital banking services to its citizens. The study uses the Technology Acceptance Model (TAM) to investigate the impact of perceived ease of use, usefulness, data security and privacy, government expectations and benefits, social influence, perceived value, and attractiveness of alternatives on Malaysians' expectations toward digital banking. This survey specifically targeted Malaysians aged 18 and above who use e-banking. There are 443 responders. However, only 400 sets may be utilized because 43 sets are invalid. The Statistical Package for the Social Science (SPSS) statistical software is used to analyze the collected data from the respondents, including demographic analysis, reliability test, and inferential analysis. The results show that perceived usefulness, perceived value, government expectations and benefits, social influence, and attractiveness of alternatives are the essential factors contributing towards the behavioural intention of digital banking. On the contrary, perceived ease of use and data security and privacy are unessential in the behavioural intention towards digital banking.